Management of adolescents with hidradenitis suppurativa. (17th November 2021) - Collier, Erin; Shi, Vivian Y.; Hsiao, Jennifer L.
Abstract: Hidradenitis suppurativa (HS) can have devastating impacts on quality of life (QoL), especially during adolescence when patients face unique challenges related to self-esteem, body-image, and sexual maturation. Many teenage HS patients also experience social challenges related to school, relationships, and employment that may require physician intervention. Strategies for comprehensive management of this special group include addressing low medication adherence, screening for comorbidities, and recommending practical lifestyle modifications to reduce disease flares. Herein, we review the impact of HS on adolescent patients and provide practical recommendations to minimize effects on the adolescent life course.